Effects of perinatal undernutrition on social transmission of food preference in adult male Wistar rats. Issue 71 (December 2018) - Rubio, Lorena; Téllez, Laura; Regalado, Mirelta; Torrero, Carmen; Salas, Manuel
Highlights: Food selection for cinnamon or cocoa in early underfed observers showed disrupted responses to the cocoa than cinnamon. Early undernutrition does not affect the basic food selection memory processes, possibly because of its role in survival. Abstract: Nutrition plays a fundamental role in learning and memory, and early experimental undernutrition interferes with brain memory processes. Social transmission of food preference (STFP) is a natural olfactory paired-associate learning test that has not been used to assess the effects of early undernutrition on memory consolidation. Male Wistar rats were randomly divided into two groups: control and early undernourished. The underfed rats received different percentages of a balanced diet during gestation. After birth, pups were underfed by alternating every 12 h between two lactating dams, one with ligated nipples. Weaning occurred on PD 25 followed by an ad lib diet until PD 90. Demonstrator rats were given powdered food mixed with cinnamon, followed by a 30-min interaction with an underfed observer. Thereafter, the observer had two choices of food: cinnamon or cocoa. During the food preference test, control and underfed OBS rats preferred the food containing cinnamon. Through social interaction, the UG OBS rats showed latency for head contacts and oral-nasal investigation was higher in the underfed rats; only head contacts and oral-nasal investigation frequency was lower; with the duration lower, but oral-nasal investigation duration was higher (p < 0.05). In the preference phase, the OBS underfed rat latencies for both stimuli were prolonged, the frequency lower only for cocoa, and the duration lower for cinnamon but higher for cocoa (p < 0.05). Findings suggested that early undernutrition interfered with the attentive social transmission to take a decision during the preference phase, but not with the short-term memory consolidation of social food preference.